2021
DOI: 10.1155/2021/6634601
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs: Novel Players in the Oxidative Stress‐Mediated Pathologies, Biomarkers, and Therapeutic Targets

Abstract: Oxidative stress (OxS) is a wildly described cause of damage to macromolecules, resulting in abnormal physiological conditions. In recent years, a few studies have shown that oxidation/antioxidation imbalance plays a significant role in developing diseases involving different systems and organs. However, the research on the circular RNA (circRNA) roles in OxS is still in its very infancy. Therefore, we hope to provide a comprehensive overview of the recent research that explored the function of circRNAs associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…One fundamental mechanism of action of circRNAs is mediated by their ability to bind and sponge out specific miRNAs, therefore regulating the expression of their target mRNAs. Mounting evidence has indicated the dysregulation of the circRNA–miRNA–mRNA interaction network in the pathogenesis of many diseases [ 51 ], including oxidative stress-mediated pathologies [ 21 , 52 , 53 ]. To reveal potential interaction networks of circANKRD12 triggered by oxidative stress in ECs, we designed two pipelines using online prediction tools and the dataset of transcriptomic changes induced by H 2 O 2 treatment in HUVEC cells we had previously published [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…One fundamental mechanism of action of circRNAs is mediated by their ability to bind and sponge out specific miRNAs, therefore regulating the expression of their target mRNAs. Mounting evidence has indicated the dysregulation of the circRNA–miRNA–mRNA interaction network in the pathogenesis of many diseases [ 51 ], including oxidative stress-mediated pathologies [ 21 , 52 , 53 ]. To reveal potential interaction networks of circANKRD12 triggered by oxidative stress in ECs, we designed two pipelines using online prediction tools and the dataset of transcriptomic changes induced by H 2 O 2 treatment in HUVEC cells we had previously published [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…These were affected by mRNAs like Atp6v0a1, Atp6v0b, Atp6v0c, and Atp6v0e2 which were then involved in the miRNA-circRNA interaction network involved in the progression of the Nrf-2 mediated development of RA. 134 The effect of circRNA is extremely underlying and has far reaching effect on the progression of the disease. Recent research has verified that epigenetically regulated gene networks in the peripheral blood mononuclear cells consequently result in the severity regulation of RA.…”
Section: Ramentioning
confidence: 99%
“…Stability, unlike linear RNA, circRNAs is a single-stranded, covalent closed-loop structure without a 5′ cap structure and a 3′ terminal ploy(A) tail. This structure may protect it from degradation by RNA exonuclease (RNAser) and thus has higher stability than linear RNA ( Suzuki and Tsukahara, 2014 ; Di Timoteo et al, 2020 ; Wang et al, 2021h ). Conservative, circRNAs is highly conserved across species ( AbouHaidar et al, 2014 ; Mao et al, 2021 ; Meyer et al, 2021 ).…”
Section: Biogenesis and Classification Of Circular Rnasmentioning
confidence: 99%
“…Studies have shown that circRNAs are abundant and stable in exosomes, and some circRNAs are more highly expressed in blood than in tissues ( D'Ambrosi et al, 2021 ; Reese and Dhayat, 2021 ; Tian et al, 2021 ; van Zonneveld et al, 2021 ). The high expression and stability of circRNAs in body fluids would be more beneficial for their clinical applications ( Bu et al, 2021 ; Fontemaggi et al, 2021 ; Wang et al, 2021h ; Zhao et al, 2021 ). However, despite the identification of thousands of tissue- and disease-specific circRNAs by RNA-seq ( Kaushik et al, 2021 ; Tian-Zhao et al, 2021 ), the understanding of the mechanism of circRNAs generation and biological functions is limited at this stage.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%